Table of Content - -, (Journal of Curriculum and Teaching Methodology, 2024)
Table of Content:1. Beliefs of Arabic language teachers towards employing active learning in first-year basic education schools in Sultanate of OmanDr. Humaid Muslem Alsaidi, Mr. Arif Rabiaa Alyazidi2. Analysis of book 4 in light of the requirements of the science, technology engineering, and mathematics (STEM) approach in the Kingdom of Saudi Arabia (build a suggested pro-posal)Researcher/ Maha Mohammed Shamroukh Al-Otaibi, Dr. Abdullah Awad Abdullah Al-Harbi3. The impact of digital storytelling on motivation and achievement in teaching scientific concepts for Kindergarten childrenResearcher/ Najma Bint Nasser Al-Jabriya4. Ethical Issues Related to Low Performance Among Saudi Students in the Trends in International Mathematics and Science Study (TIMSS)Noha Ali Almazroo
Keywords: Journal of Curriculum and Teaching Methodology